MENINGKATKAN KOMPETENSI PROFESIONAL KONSELOR DALAM PEMBENTUKAN KARAKTER CERDAS SISWA MIN SUNGAI TARAB (SEBUAH PILOTING PROJECT DI MIN SUNGAI TARAB) - HADIARNI HADIARNI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
This research was aimed at conducting a piloting project on improving professional competency of guidance teacher in promoting smart character of Islamic Elementary School (MIN) Sungai Tarab). To achieve the goal, qualitative approach and collaborative action research were employed. The subjects of the research were a guidance teacher and other school personnels. The subjects were chosen by means of purposive sampling technique since they were chosen in line with the purpose of the research. Data were collected by following the principles qualitative paradigm where the researcher was the key instrument, and observation, interview and documentary study were used. The research steps basically followed those of action research. Those steps were: 1) Intial reflction, 2) Planning, 3) action and observation, dan 4) reflection. Data analysis was carried out during data collection by referring to Miles dan Huberman’s which consisted of three main steps: 1) data reduction, 2) data display, and 3) conclusion/verification. The finding of this research show that the delopment took place for several indicators of professional competency of the guidance teacher in terms of improving her horizon and knowledge and skill in administering and following up inventory (AUM) while other indicators cannot be improve due to time constrains from the subject of the research.Kata kunci: kompetensi profesional, konselor, karakter cerdas, MIN Sungai Tarab